SOME CHANGES OF REPRODUCTION FISH IN PONDS WITH VIOLATED ECOLOGICAL REGIME - N. I. Rabazanov; M. M. Shikhshabekov (Юг России: экология, развитие, 2014)
The main aim of the article is to study the reproduction and study of gametogenesis (ovo-and spermatogenesis) of many valuable as commercial and of yet not covered by the fishery of species of fishes for various reasons from different taxonomic groups with a different biology. The study of gametogenesis of representatives of different ecological groups (freshwater, marine) allowed not only to establish the regularities, but also reveal features of their proceeding in an ecological conditions of water bodies that have changed due to human influence, and also to note the adaptive changes and to correlate processes occurring in different levels of life.